Analisis Tingkat Persepsi Mahasiswa terhadap Mata Kuliah Ulumul Hadis dan Faktor-Faktor yang Mempengaruhinya - Azzahra, Arini Nabila; Suismanto, Suismanto; Rokhimawan, Mohamad Agung (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
Ulumul Hadis is a fundamental discipline within Islamic studies and serves as a core course at State Islamic Higer Education Institutions (PTKIN), including UIN Sunan Kalijaga Yogyakarta. Despite its importance, the course is often perceived as difficult and less appealing to students. This study aims to examine the perception level of students in the Early Childhood Islamic Education (PIAUD) program toward the Ulumul Hadis course and to identify the internal dan external factors influencing it. The study employed a quantitative approach with an explanatory design, involving 73 second-semester students ffrom a total population of 89. Data were collected through questionnaires and analyzed using descriptive statistics and multiple linear regression. The findings indicate that students generally hold a positive perception of the Ulumul Hadis course, with an average score of 19,589 out of a maximum of 25,00. Regression analysis revealed that internal factors such as motivation and prior understanding were more dominant (B=2,236) than external ones (B=1,673). These findings suggest that students’ internal readiness plays a crucial role in shaping positive perceptions. This study contributes to curriculum development and instructional strategies, particularly in aligning Islamic studies content with the context of early childhood education.